2021
DOI: 10.1371/journal.pone.0252231
|View full text |Cite
|
Sign up to set email alerts
|

Abundance estimation for line transect sampling: A comparison of distance sampling and spatial capture-recapture models

Abstract: Accurate and precise abundance estimation is vital for informed wildlife conservation and management decision-making. Line transect surveys are a common sampling approach for abundance estimation. Distance sampling is often used to estimate abundance from line transect survey data; however, search encounter spatial capture-recapture can also be used when individuals in the population of interest are identifiable. The search encounter spatial capture-recapture model has rarely been applied, and its performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Detectability can be influenced by population density, distribution characteristics (i.e. open or closed population; Crum et al., 2021; Dambly et al., 2021; Westcott et al., 2012), landscape heterogeneity (Barata et al., 2017; Nuno et al., 2013; Rhodes & Jonzén, 2011), observer experience (Barata et al., 2017; Vallecillo et al., 2021) and weather conditions during monitoring (Morant et al., 2020). While we did not directly assess detectability bias and its effects on accuracy of counts in our study system, our analysis (Appendix SA) revealed that WMU‐level variability in population density and dense coniferous forest cover contributed to greater among‐plot variability and thus more imprecise population estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detectability can be influenced by population density, distribution characteristics (i.e. open or closed population; Crum et al., 2021; Dambly et al., 2021; Westcott et al., 2012), landscape heterogeneity (Barata et al., 2017; Nuno et al., 2013; Rhodes & Jonzén, 2011), observer experience (Barata et al., 2017; Vallecillo et al., 2021) and weather conditions during monitoring (Morant et al., 2020). While we did not directly assess detectability bias and its effects on accuracy of counts in our study system, our analysis (Appendix SA) revealed that WMU‐level variability in population density and dense coniferous forest cover contributed to greater among‐plot variability and thus more imprecise population estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Detectability can be influenced by population density, distribution characteristics (i.e. open or closed population;Crum et al, 2021;…”
mentioning
confidence: 99%
“…When the conservation goal is to assess abundance in an area at a specific time, line transect surveys may be a cost-effective choice. However, if one’s goal is to estimate the number of animals in an area over a longer period, CR methods could be more appropriate but have cost implications that may exceed those of conducting a line transect survey (Crum, Neyman, & Gowan, 2021; Hammond et al, 2021). Despite differences in ecological inference, DS and CR are complementary methods depending on the conservation motivations and funding.…”
Section: Discussionmentioning
confidence: 99%
“…line transect monitoring), while CR monitoring programs can be costly to develop at large spatial scales because more sampling effort is required over a longer time period to recapture individuals (Hammond et al, 2021). Even when estimating abundance over the same study area, DS and CR do not estimate exactly the same quantity (Calambokidis & Barlow, 2004;Crum, Neyman, & Gowan, 2021). DS methods estimate abundance within a study area at the time of the survey.…”
Section: Introductionmentioning
confidence: 99%
“…Unbiased estimates of species density and abundance are critical to understand population evolutionary processes in order to assess and select conservation management actions ( Rowcliffe et al, 2011 ; Crum, Neyman & Gowan, 2021 ; Amburgey et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%